Resistance to mTOR Kinase Inhibitors in Lymphoma Cells Lacking 4EBP1 - Mallya, Sharmila; Fitch, Briana A.; Lee, J. Scott; So, Lomon; Janes, Matthew R.; Fruman, David A. (PLOS ONE, 2014)
Inhibitors of the mechanistic target of rapamycin (mTOR) hold promise for treatment of hematological malignancies. Analogs of the allosteric mTOR inhibitor rapamycin are approved for mantle cell lymphoma but have limited efficacy in other blood cancers. ATP-competitive “active-site” mTOR inhibitors produce more complete mTOR inhibition and are more effective than rapamycin in preclinical models of leukemia, lymphoma and multiple myeloma. In parallel to clinical trials of active-site mTOR inhibitors, it will be important to identify resistance mechanisms that might limit drug efficacy in certain patients. From a panel of diffuse large B-cell lymphoma cell lines, we found that the VAL cell line is particularly resistant to apoptosis in the presence of active-site mTOR inhibitors. Mechanistic investigation showed that VAL does not express eukaryotic initiation factor 4E-binding protein-1 (4EBP1), a key negative regulator of translation controlled by mTOR. Although VAL cells express the related protein 4EBP2, mTOR inhibitor treatment fails to displace eukaryotic initiation factor 4G from the mRNA cap-binding complex. Knockdown of eukaryotic initiation factor 4E, or re-expression of 4EBP1, sensitizes cells to apoptosis when treated with active-site mTOR inhibitors. These findings provide a naturally occurring example of 4EBP deficiency driving lymphoma cell resistance to active-site mTOR inhibitors.